Marketing Jasa di Institusi Pendidikan (Analisis Pemasaran dalam Pendidikan) - Moch. Khafidz Fuad Raya (STAIFAS-Press, 2016)
The entry of a business concept (corporate) into the world of education has changed people's negative outlook towards education. Education becomes a commodity to be traded land. Massive campaign conducted mass then seasoned by the actions of KKN (corruption, collusion and nepotism) and payments will be the case most common in Indonesia. That fact has been tarnished for educational institutions, and blame the marketing concept which has been used. If examine comprehensively and thoroughly, marketing activities did not constitute a